Functions of human neutrophilic granulocytes after in vivo exposure to interferon alpha. - Einhorn, S (1984)
The ability of neutrophilic granulocytes to phagocytize yeast particles and to reduce Nitro Blue Tetrazolium at rest and on activation with bacterial stimuli was monitored in 32 patients receiving treatment with human interferon alpha. The ability of these cells to attach to and ingest yeast particles was not altered to any major extent during 1 year of interferon treatment. In most patients, the Nitro Blue Tetrazolium-reducing activity increased after the first injection of interferon. During prolonged treatment with interferon alpha, 1 week to 1 year, granulocytes activated with bacteria exhibited a reduced Nitro Blue Tetrazolium activity in most patients.